Financial viability analysis for green hydrogen production opportunity from hydropower plant’s excess power in Indonesia - Hardana, Hendy Eka; Adiwibowo, Pupung; Sunitiyoso, Yos; Kurniawan, Tri Edi Kusuma (Center of Biomass & Renewable Energy (CBIORE), 2024)
The research presents a comprehensive analysis of the financial viability of producing green hydrogen from excess power generated by small hydropower plants in Indonesia. It highlights Indonesia’s commitment to increasing renewable energy sources to achieve net zero emissions by 2060 and the role of Perusahaan Listrik Negara (PLN) in this transition. The study examines the potential of utilizing dormant excess power from retroactive small hydropower plants to produce green hydrogen, which could significantly decarbonize hard-to-abate sectors and enhance energy security. The authors conducted a financial analysis using the NREL H2A Production Model to determine the optimal technical arrangement and financial simulation for green hydrogen production. The paper discusses various electrolyzer technologies, with a focus on alkaline water electrolyzers due to their high technology readiness level and low capital expenditure. It also explores the sensitivity of the levelized cost of hydrogen to different factors, particularly the cost of utilities. The findings suggest that green hydrogen production from small hydropower plants is economically feasible in Indonesia, with the potential to contribute to the global hydrogen market and support the country’s green circular economy. The study concludes that green hydrogen production using excess electricity from small hydropower plants is a viable method for decarbonization and offers scalability for future energy production in Indonesia, with the first initial step being as a green hydrogen and natural gas co-firing fuel mixing in gas turbines.